Influences of poly(butylene adipate-co-terephthalate) on soil microbiota and plant growth. (July 2016) - Muroi, Fumihiro; Tachibana, Yuya; Kobayashi, Yukiko; Sakurai, Takanori; Kasuya, Ken-ichi
Abstract: We investigated changes in soil microbiota associated with the degradation of poly(butylene adipate- co -terephthalate) (PBAT) film at 30 °C using a polymerase chain reaction-denaturing gradient gel electrophoresis (PCR-DGGE) method. The analysis revealed that fungal flora in soil in the vicinity of film surface (FS) drastically changed after incubation for 7 months. Phylogenetic analysis showed that fungi belonging to the phylum Ascomycota were enriched on the FS. In addition, the presence of PBAT affected the growth of specific fungal species in bulk soil (BS). On the other hand, compositions of the bacterial flora formed in both BS and FS were not strongly influenced by the presence of PBAT. Plant growth-promoting rhizobacteria (PGPR), genera Azospirillum and Mesorhizobium, were detected in both environments, i.e., in BS and FS, during the course of 7-month incubation. In terms of plant growth, the growth of Brassica rapa var. chinensis was not negatively affected in BS after 7 month compared with that in the control soil (CS), indicating that changes in the soil microbiota because of the addition of PBAT have little influence on the growth of B . rapa var. chinensis .